1999
DOI: 10.1046/j.1525-1594.1999.06214.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Three‐Dimensional Finite Element Analysis of Newly Designed Cementless Total Hip Stems

Abstract: We designed 2 new types of proximally coated stems (the FMS and FMS-anatomic) based on the endosteal geometry of femora with congenital dislocation or dysplastic hip. The FMS was symmetric while the FMS-anatomic was asymmetric. We compared the proximal fit and fill to the femoral canal, contact stress, relative motion, and load transfer to the femur of 5 stems (FMS, FMS-anatomic, Omnifit, Omniflex, and individual stem) using three-dimensional computer simulation and finite element analysis. The FMS and FMS-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…The implant fills the endosteal canal to a high percentage; 83.10% at anteroposterior view and 71.70% at mediolateral view. The comparison between different cementless stems [13,20] is illustrated in Figure 7. This newly designed stem was among the highest percentage of fit and fill compared to others except the Fukui Medical School (FMS and FMS-A), and IDS stem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implant fills the endosteal canal to a high percentage; 83.10% at anteroposterior view and 71.70% at mediolateral view. The comparison between different cementless stems [13,20] is illustrated in Figure 7. This newly designed stem was among the highest percentage of fit and fill compared to others except the Fukui Medical School (FMS and FMS-A), and IDS stem.…”
Section: Resultsmentioning
confidence: 99%
“…The intact femora consisted of 5000 nodes and 34 000 elements, and the ‘virtual surgery femora’ consisted of 7900 nodes and 41 900 elements. The material properties of the cementless femoral stem were assigned as titanium alloy (Ti 6 Al 4 V) with Young’s Modulus of 110 GPa and a Poisson’s ratio of 0.3 [13]. In addition, the femora were assumed as isotropic and linear elastic, with bone properties determined according to the CT datasets grey level values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed a femoral flare of 3.71 at 10 mm above the zero level that gradually stabilized at the diaphyseal region as illustrated in Figure 7. Several studies in Japan considered these differences when they designed implants and focused on the metaphyseal region anterolaterally flared for loading purposes [1720, 46]. Laine et al emphasized the selection of the cementless stem from the metaphyseal region (MCFI) rather than the CFI [10].…”
Section: Discussionmentioning
confidence: 99%
“…Biological fixation can be achieved by comprehending the morphology of the proximal femur prior design to achieve an optimum fit, fill implant, and promote bone ingrowth. Several studies in Japan emphasized obtaining precise information about the endosteal canal in a proximal femur, which is essential for metaphyseal support for cementless hip stems [1721]. These researchers developed the cementless femoral stem that was specifically designed for dysplastic hips with proximal fitting anterolaterally flared stems, which has showed promising results.…”
Section: Introductionmentioning
confidence: 99%